PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 015 KOTA GARO KECAMATAN TAPUNG HILIR KABUPATEN KAMPAR - Wiwik Handayani; Hendri Marhadi; Syahrilfuddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Background problem in this study is the low student learning outcomes in social studies. Based on initial observations that the author did, that the learning outcomes of fourth grade students of SDN 015 Tapung Hilir Subdistrict Garo City Kampar regency less than the maximum. Of the 22 students obtained an average grade of 63.86, and 12 students (55%) have not yet reached a value above the minimum completeness criteria (KKM) has been established, while the KKM predetermined namely 70. The study was conducted in SDN 015 Garo City Tapung Hilir Subdistrict Kampar Regency in fourth grade social studies, while the time the study was conducted in the academic year 2015/2016. The results of this study indicate that the learning outcomes of students on average from a base score of 68.86 increased in the first cycle with the average being 68.18 compared with a base score, which means the increase is 4:32. In the second cycle average of 73.86 an increase of 10 points from the average score of basic, so overall there is an increase of 16% from the average score of the base. By the results, it can be concluded that the activities of teachers and students at each meeting has increased and the results of social studies students also increased. This proves that the model type STAD cooperative learning can improve learning outcomes IPS grade IV SDN 015 Garo City Tapung Hilir District of Kampar. Keywords: Learning Outcomes IPS, STAD